# Math

posted by .

Suppose an odd function f has an inverse g. Prove that g is also odd.

• Math -

f(-x) = -f(x)

x = g(y)
-x = g(-y) but -x = -(g(y)) = -g(y)
so, g is odd

## Similar Questions

1. ### discrete math

use a direct proof to show that the product of two odd numbers is odd. Proofs: (all the nos. i used are odd) 3 x 3 = 9 5 x 9 = 45 7 x 3 = 21 Yes, but you didn't prove the statement for "all" odd integers, only the odd integers you …
2. ### discrete math

prove that if n is an integer and 3n+2 is even, then n is even using a)a proof by contraposition b)a proof by contradiction I'll try part b, you'll have to refresh me on what contraposition means here. Here is the claim we start with …
3. ### odd and even functions

Using f is odd if f(-x) = -f(x) or even if f(-x) = f(x) for all real x, how do I 1)show that a polynomial P(x) that contains only odd powers of x is an odd function 2)show that if a polynomial P(x) contains both odd and even powders …
4. ### Math

Let f and g be two odd functions. Prove that: a) f + g is an odd function b) g of f is an odd function I am not even sure where to start, any help that can be provided would be appreciated!
5. ### college algebra

Let f denote an odd function and g an odd function. Decide whether the function h(x)=g(x) f(x) is even or odd.
6. ### Maths

The first odd number can be expressed as 1 = 1squared - 0squared. The second odd number can be expressed as 3 = 2squared - 1squared. The third odd number can be expressed as 5 = 3squared - 2squeared. a) Express the fourth odd number …